2021
DOI: 10.1038/s41598-021-99875-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability predictions of therapeutic monoclonal antibodies in solution using Arrhenius-based kinetics

Abstract: Long-term stability of monoclonal antibodies to be used as biologics is a key aspect in their development. Therefore, its possible early prediction from accelerated stability studies is of major interest, despite currently being regarded as not sufficiently robust. In this work, using a combination of accelerated stability studies (up to 6 months) and first order degradation kinetic model, we are able to predict the long-term stability (up to 3 years) of multiple monoclonal antibody formulations. More specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
2
39
0
1
Order By: Relevance
“…Recently, Kuzman et al and Gentiluomo et al have shown some potential for predicting long-term shelf-life stability when using non-linear machine learning models. 32 , 33 This, however, also leads to some challenges when assuming first-order kinetics of proteins that may be susceptible to different degradation pathways that may affect chemical and physical stability upon exposure to thermal stress. 34 Therefore, the accelerated stability and real-time stability measurements are different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kuzman et al and Gentiluomo et al have shown some potential for predicting long-term shelf-life stability when using non-linear machine learning models. 32 , 33 This, however, also leads to some challenges when assuming first-order kinetics of proteins that may be susceptible to different degradation pathways that may affect chemical and physical stability upon exposure to thermal stress. 34 Therefore, the accelerated stability and real-time stability measurements are different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Such non-linear degradation over time, as detected for HMWP formation of SAR441255, is also often observed for several (e.g., aggregation related) quality attributes of vaccines and therapeutic antibodies [25,[34][35][36][37]49,[51][52][53][54], underlining the benefit of screening various kinetic models for biopharmaceutics. With appropriate kinetic models that accurately describe the degradation progress as a function of time and temperature, various applications emerge, such as estimation of shelf life [34][35][36][37][38], accurate degradation-based predictions for products during various types of temperature excursions [35,38,49], ranking of formulations [37,39,49], batch-to-batch comparisons and real-time shelf-life monitoring of products during shipments [39,40,49].…”
Section: Discussionmentioning
confidence: 82%
“…Very recently, Kuzman et al [25] successfully used Arrhenius-based kinetics to predict long-term stability of IgG1, IgG2, and fusion proteins. For some key stability attributes such as sum of aggregates by SEC, accurate predictions of long-term stability were obtained using first-order kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations